Evaluation of hypoglycemic activity of methanolic extract of Acorus calamus (linn). roots in alloxan induced diabetes rat model - D., Prashanth; Ahmed, Fazeel Zubair (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To evaluate hypoglycemic activity of methanolic extract of roots of Acorus calamus (AC) in alloxan induced diabetic albino rats and to compare with standard oral hypoglycemic drug glibenclamide. Methods: A total of 54 rats were used for this study. The study was done in two phases. In phase I, oral glucose tolerance test was done in 4 groups at 0, 30, 60 and 120 minutes after administration of AC in 3 different doses – 100, 150 and 200mg/kg to 3 different groups, with control being the fourth group. The dose of AC which caused maximal blood glucose lowering was selected for phase II. In phase II, rats were divided into 5 groups. First 2 groups were non diabetic groups which were given distilled water (DW) and AC respectively. Next 3 groups were alloxan induced diabetic groups which were given DW, AC and Glibencamide 0.5mg/kg po respectively. All drugs were given for 28 days and FBS was measured on 0, 3, 7, 14, 21, and 28th days. Results: In phase I, both AC 150 and 200mg/kg lowered blood glucose but their effect was comparable and thus lower dose - 150mg/kg was selected for phase II. In phase II, among non-diabetic groups, AC 150 mg/kg produced significant hypoglycemia in comparison with control group. Among diabetic groups, both AC 150 mg/kg and glibenclamide 0.5 mg/kg produced significant hypoglycemia in comparison with control group on all days. On days 3 and 7, hypoglycaemic action of AC 150mg/kg was not as much as Glibenclamide (p <0.05), but on days 14, 21 and 28, the hypoglycaemic action of AC 150 mg/kg was comparable to Glibenclamide 0.5mg/kg. (P >0.05). Conclusions: AC 150mg/kg causes hypoglycemia in alloxan induced diabetic rats as well as nondiabetic rats.